HAND SIGNS IN THE LERANING OF TRADITIOINAL ANGKLUNG INSTRUMENTS IN SMA NEGERI 1 BABALAN PANGKALAN BRANDAN - Julio Pegenusa; Uyuni Widiastuti; Herna Hirza (Universitas Negeri Medan, 2020)
This research is the Use of Hand Signs in Learning Angklung traditional musical instruments in SMA Negeri 1 Babalan. The purpose of this study was to determine the learning process of Angklung traditional musical instruments in SMA Negeri 1 Babalan, to determine the use of hand signs in learning angklung traditional music, to determine the difficulties faced by students from using Hand Signs in learning traditional angklung music at SMA Negeri 1 Babalan, to know the student's learning ability in understanding the use of hand signs in the learning of traditional angklung music in SMA Negeri 1 Babalan. The theory used in this research is the theory of Hand Signs, learning, angklung traditional music, difficulties and learning abilities. The method used in this research is a descriptive method with a qualitative approach which includes several aspects: Observation of observation, interviews, documentation and study of literature. This research was carried out in SMA Negeri 1 Babalan, North Sumatra, located at Jalan Melati number 2 Kec. Babalan City of Pangkalan Brandan postal code 20857 North Sumatra. When this research was conducted from April 2019 to June 2019.